Antibiotics Sensitivity Pattern of Coliform Bacteria isolated From Well Water Samples in Ipetumodu, Before and After Solar Disinfection - Fakorede, C. N.; Olayinka, A. A.; Udoegbulam, C. A.; Olonisola, A. A. (Journal of Science, Technology and Innovation Research, 2026)
Microbial quality of portable water is a major public health concern in developing countries. This is because the primary domestic source of the water is usually from untreated groundwater. This study assessed the bacteriological quality of well water in Ipetumodu, South-western, Nigeria. Additionally, the solar disinfection (SODIS), and antibiotic sensitivity of coliform isolates were evaluated. Five different hand-dug well water samples (in duplicate) were cultured on Eosin Methylene Blue agar using the membrane filtration technique. Parallel aliquots were exposed to direct sunlight for six hours. The pH of the water samples ranged from 5.91 to 6.17. The results revealed that the coliform counts before SODIS ranged from 4.8×10 to 1.2×10² CFU/100mL and were reduced to 0–8.0 CFU/100mL after SODIS, with complete microbial elimination in two wells. The most recovered isolates were Klebsiella, Salmonella, Shigella, and Enterobacter species. Most of the bacteria exhibited high resistance to most of the tested antibiotics like Augmentin (100%), Cefuroxime (100%), and Cefixime (92%). Overall, the findings showed that hand-dug well water in Ipetumodu does not meet national (NAFDAC) or World Health Organization microbiological standards for potable water and is unsafe for consumption without treatment. SODIS represents a feasible, low-cost option for improving water safety but should be integrated with broader interventions and antibiotic stewardship to achieve consistent safety.